STUDI DESKRIPTIF TERHADAP MOTIVASI BELAJAR SISWA KELAS XI DI SMK TARUNA MANDIRI - Resna Suria Mauki; Ecep Supriatna; Reza Pahlevi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Motivation is one of the things that affect the success of student learning activities at school, without motivation, the learning process will be difficult to implement optimally. This is because learning motivation is a conscious and planned effort that will encourage a person to realize every goal and ideal in his life. The purpose of this study is to determine the extent of learning motivation possessed by the students of class XI Smk Taruna Mandiri Cimahi. The method used in this research is descriptive quantitative research method with probability sampling technique, with the results obtained that more than 60% of respondents have high learning motivation, while 30% of students are still in the medium category, and 10% are in the high category. low category. This proves that there are still many students who have high learning motivation within themselves. Keywords: : Learning Motivation, High School Students